2022
DOI: 10.17508/cjfst.2022.14.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of using edibleinsects as alternative protein source

Abstract: There is an urgent need for alternative protein sources due to the rapid population growth, climate change, environmental degradation by pollution, food-fuel competition and the reduction in arable land for agricultural use. Conventional livestock production is also deleterious to the environment due to the production of greenhouse gasses and ammonia. This article provides insights into the potentials of edibleinsects as novel food ingredients. The manuscript provides concise explanations for the need of embra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is because insects are poikilothermic in which energy is not required to maintain the body temperature. Thus, the abundance of energy obtained from their feed will be utilised in their reproduction and growth which efficiently impacts on FCR (Abdullahi et al, 2022;Lange and Nakamura, 2023). Therefore, black ants Smith, require less feed than crickets and are considered to have a higher feed efficiency.…”
Section: Feed -Meat Conversion Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…This is because insects are poikilothermic in which energy is not required to maintain the body temperature. Thus, the abundance of energy obtained from their feed will be utilised in their reproduction and growth which efficiently impacts on FCR (Abdullahi et al, 2022;Lange and Nakamura, 2023). Therefore, black ants Smith, require less feed than crickets and are considered to have a higher feed efficiency.…”
Section: Feed -Meat Conversion Efficiencymentioning
confidence: 99%
“…In addition, edible insects farming is considered more economical than conventional livestock farming. This is attributed to the fact that insect farming only requires significantly less space, land, and water resources than livestock farming (Testa et al, 2017;Abdullahi et al, 2022). Doreau et al (2012) demonstrated that approximately 70% of water is utilised in agricultural practices including livestock farming.…”
Section: Edible Insects' Farmingmentioning
confidence: 99%
“…The use of edible inks is not only limited to printing on food products, but can be extended to printing on edible paper, wafer paper, and icing sheets. 5 The development of edible ink technology has come a long way since its inception. The earliest forms of edible ink were made from vegetable dyes and were limited in color range and print quality.…”
Section: Introductionmentioning
confidence: 99%
“…The use of edible inks is not only limited to printing on food products, but can be extended to printing on edible paper, wafer paper, and icing sheets. 5…”
Section: Introductionmentioning
confidence: 99%